2018
DOI: 10.1101/497024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase transition and amyloid formation by a viral protein as an additional molecular mechanism of virus-induced cell toxicity

Abstract: Henipaviruses are severe human pathogens responsible for severe encephalitis. Their V protein is a key player in the evasion of the host innate immune response. We have previously reported a biophysical characterization of the Henipavirus V proteins and shown that they interact with DDB1, a cellular protein that is a component of the ubiquitin ligase E3 complex. Here, we serendipitously discovered that the Hendra virus V protein undergoes a liquidhydrogel phase transition. By combining experimental and bioinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 98 publications
2
7
0
Order By: Relevance
“…Although this protein is classified as a strong polyampholyte (FCR = 0.364, |NCPR| = 0.164), NaCl does not affect its ability to form aggregates (at least up to 300 mM). In support for the hypothesis of the involvement of π–π interactions, the most amyloidogenic region contains three contiguous tyrosine residues whose replacement with alanine residues abrogates fibrillation [ 147 ]. Finally, we can cite the case of γ44-gliadin, a wheat storage protein with an intrinsically disordered domain that undergoes LLPS in a salt-dependent manner in spite of its very weakly charged nature (FCR = 0.04 and NCPR = 0) [ 148 ].…”
Section: Relevance Of Charge Decoration In Phase Separationmentioning
confidence: 96%
See 1 more Smart Citation
“…Although this protein is classified as a strong polyampholyte (FCR = 0.364, |NCPR| = 0.164), NaCl does not affect its ability to form aggregates (at least up to 300 mM). In support for the hypothesis of the involvement of π–π interactions, the most amyloidogenic region contains three contiguous tyrosine residues whose replacement with alanine residues abrogates fibrillation [ 147 ]. Finally, we can cite the case of γ44-gliadin, a wheat storage protein with an intrinsically disordered domain that undergoes LLPS in a salt-dependent manner in spite of its very weakly charged nature (FCR = 0.04 and NCPR = 0) [ 148 ].…”
Section: Relevance Of Charge Decoration In Phase Separationmentioning
confidence: 96%
“…Examples also exist where salt, namely NaCl, does not exert any significant impact on LLPS, suggesting that the formation of coacervates relies on hydrophobic interactions. An illustrative example is provided by PNT3, a viral protein region that undergoes LLPS with concomitant formation of amyloid-like fibrils [ 147 ]. Although this protein is classified as a strong polyampholyte (FCR = 0.364, |NCPR| = 0.164), NaCl does not affect its ability to form aggregates (at least up to 300 mM).…”
Section: Relevance Of Charge Decoration In Phase Separationmentioning
confidence: 99%
“…In the same vein, the V protein from Hendra virus (HeV, a paramyxovirus) was shown to undergo a liquid-to-gel phase transition in vitro. The minimal V region responsible for this property, referred to as PNT3, has been identified within the intrinsically disordered N-terminal domain of V [207]. PNT3 was found to form amyloid-like fibrils both in the liquid and hydrogel state.…”
Section: Examples Of Llps-mediated Viral Interference With Functions mentioning
confidence: 99%
“…In line with these properties, we previously reported that HeV V jellifies in vitro. The minimal HeV V region responsible for this ability (referred to as PNT3, aa 200-310 of HeV V) was identified within its intrinsically disordered NTD [82,83]. Binding assays to an amyloid-specific dye and negative-staining transmission electron microscopy (TEM) studies, showed that PNT3 forms amyloid-like fibrils [82,83].…”
Section: Phase Separation and Fibrillation Abilities Of The W Proteinsmentioning
confidence: 99%